The Evolution of Masculine Vulnerability in Selected Lyrics of Rich Brian (2017-2025) - Aurelia Sitanggang; Irma Rahmawati (Locus Journal of Academic Literature Review, 2026)
This article examines the development of masculine vulnerability in selected lyrics by Rich Brian from 2017 to 2025. This study is based on the difference between the concept of hegemonic masculinity, which positions men as strong, rational, confident, and able to control their emotions, and the development of contemporary hip-hop, which increasingly provides space for men to express emotional experiences such as pain, anxiety, self-doubt, and self-reflection. This study uses a qualitative descriptive method with a thematic analysis approach to examine four Rich Brian songs, namely Glow Like Dat, Kids, New Tooth, and She. The findings show that masculine vulnerability in Rich Brian’s lyrics is represented through various emotional experiences, including emotional wounds, anxiety, inner conflict, personal struggles, emotional openness, and self-reflection. The study also finds that these lyrics do not completely reject the concept of hegemonic masculinity because elements such as ambition, achievement, self-confidence, and resilience are still presented. However, these elements are combined with emotional experiences and psychological pressures experienced by men. Therefore, this article demonstrates that Rich Brian’s lyrics portray masculinity as a dynamic, flexible, and continuously evolving identity in contemporary hip-hop, where strength and vulnerability can exist together.